Bed Management Strategy for Overcrowding at the Emergency Department: A Systematic Review - Tampubolon, L; ., Pujiyanto (KnE Life Sciences, 2018)
ED crowding has become an emerging threat to patient safety and health systems worldwide. As the problem of ED crowding continues to evolve, it is important to see factors that influence the overcrowding at the emergency department. Hospital beds are a scarce resource and always in need. When the accident and emergency department admits a patient, there may not be an available bed that matches the requested speciality. Hence, the lack of available hospital beds has become a major difficulty, and changing bed-management policy could improve the patient flow. A systematic review conducted the PRISMA flowchart using online databases such as ProQuest and Google scholar with bed management, emergency department, overcrowding as keywords, restricting academic journals and articles published between 2003 and 2016. There are some factors associated with ED crowding. Identifying, developing and implementing strategies to improve the hold time required and other barriers would be important to improve patient flow. Changing policies for hospital bed management is worth exploring to improve hospital patient flow and LOS (Length of stay). With this insight, the hospital administration can be better equipped to devise strategies to reduce bed overflow and therefore improved patient care. Keywords: bed management, emergency department, overcrowding